2013
DOI: 10.1371/journal.pone.0063343
|View full text |Cite
|
Sign up to set email alerts
|

American Tegumentary Leishmaniasis: Effectiveness of an Immunohistochemical Protocol for the Detection of Leishmania in Skin

Abstract: BackgroundAmerican tegumentary leishmaniasis (ATL) is endemic in Latin America, where Brazil has over 27 thousand cases per year. The aim of the present study was to develop an immunohistochemical method (IHC) for ATL diagnosis. For this purpose, we used serum from a dog naturally infected with Leishmania (L) infantum (canine hyperimmune serum) as the primary antibody, followed by a detection system with a secondary biotinylated antibody.MethodologySkin samples were obtained from 73 patients in an endemic area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
5
22
0
5
Order By: Relevance
“…[8][9][10] These results are in agreement with our results (44%). It is important to emphasize that all patients in our study are from areas where the only parasite ever identified in cutaneous leishmaniasis has been L. (V.) braziliensis, 11,12 which makes the sensitivity of our method very good for this species of leishmania.…”
Section: Discussionsupporting
confidence: 93%
“…[8][9][10] These results are in agreement with our results (44%). It is important to emphasize that all patients in our study are from areas where the only parasite ever identified in cutaneous leishmaniasis has been L. (V.) braziliensis, 11,12 which makes the sensitivity of our method very good for this species of leishmania.…”
Section: Discussionsupporting
confidence: 93%
“…The reaction highlighted the parasitic organisms and allowed detection of small numbers of amastigotes. Cross‐reactivity between human anti‐ Leishmania hyperimmune serum and fungal forms with immunohistochemistry has been reported in humans and may occur in dogs. However, special stains such as PAS or Grocott stain may help to differentiate these diseases, and all cases in this series were negative for fungal elements with PAS stain.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitological diagnosis is definitive and consists of the microscopic examination of Giemsa-stained biopsy specimen smears, of histopathological examination or immunohistochemical approaches in lesion fragment triturates, and by parasite in vitro cultures, as well as PCR. However, these tests' sensitivity varies according to when the lesions occurred, and a low number of parasites can be present in the late lesions, hampering the sensitivity of the tests (8)(9)(10)(11)(12)(13). Additionally, these tests require invasive procedures of sample collection, which limit their use.…”
mentioning
confidence: 99%